LAYANAN PENEMPATAN DAN PENYALURAN DALAM MENENTUKAN JURUSAN/KONSENTRASI MAHASISWA JURUSAN PAI PADA FAKULTAS TARBIYAH DAN KEGURUAN UIN ANTASARI - Surawardi Surawardi; Masyithah Masyithah (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2017)
The placement and distribution service in determining the majors/ concentration of students of PAI department at the Faculty of Tarbiyah and UB Antasari Training is conducted with the Procedures and Steps of Placement and Distribution Services, namely: First, Planning, subject at the KKNI curriculum sheet at the end of the fourth semester. Second, Implementation, Since being in semester V PAI college students based on their respective concentration. Third, Evaluation, Evaluation is done only in the form of a comprehensive examination in the form of written test and oral test applicable to all concentration with exam material is also the same. Fourth, Analysis of the results of the evaluation, analysis of comprehensive exam results that passed a written exam can perform oral exams and practice. Fifth, Follow-up, as a follow-up again is where munaqasyah thesis exam still there are students who have not correct reading Al Qur'an then when doing revision after test must learn again correct reading Al Qur'an so get the signature of revision by thesis examiner. Sixth, Reports, reporting made so far for students in placement and distribution services after they have determined their preferred concentration. Placement and Distribution service techniques include: First, Documentation studies on the results of instrumentation applications and data sets, No specific instruments have been used to determine the concentration of PAI faculty of Tarbiyah and UB Antasari Banjarmasin. Second, Observation of the Physical Condition, Communication Ability, and Other Student Behavior, and Environmental Physical Conditions. Third, the study of the rules, both written and unwritten apply, the technique of student placement in determining the concentration in the department / study program of Faculty of Tarbiyah and Teacher Training through the study of written rules and actually already exist in the academic script on the curriculum sheet of the department of PAI which regulates the distribution courses tailored to their respective concentrations. Fourth, Prospective and Conducive Environmental Conditions Study for Student Development, a perspective and conducive environmental condition study technique for the development of students in determining the type of concentration they choose in the PAI Department of Faculty of Tarbiyah and Teacher Training of UIN Antasari is to provide guidance that there is a certain concentration which is more prospective considering the limitations of teachers available to religious schools today. Fifth; Interview with related parties. Keywords: Service, placement and distribution, determining department/concentration